2012
DOI: 10.1128/aac.05280-11
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Temporal Evolution of Pfcrt and Pfmdr1 Genotypes and Plasmodium falciparum In Vitro Drug Susceptibility to 4-Aminoquinolines after Drug Policy Change in French Guiana

Abstract: Analysis of the evolution of drug target genes under changing drug policy is needed to assist monitoring of Plasmodium falciparum drug resistance in the field. Here we genotype Pfcrt and Pfdmr1 of 700 isolates collected in French Guiana from 2000 (5 years after withdrawal of chloroquine) to 2008, i.e., the period when the artemether-lumefantrine combination was progressively introduced and mefloquine was abandoned. Gene sequencing showed fixation of the 7G8-type Pfcrt SMVNT resistance haplotype and near fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
5
22
0
1
Order By: Relevance
“…Genomic DNA was prepared using the QIAmp DNA Blood Kit (Qiagen). Conditions for PCR and targeted sequencing of pfcrt exon 2 (harboring codons 72-76) and polymorphic regions of pfmdr1 were previously described (16). A 121-bp fragment encompassing the complete exon 10 of pfcrt (harboring codon 350) was PCR-amplified and Sanger-sequenced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was prepared using the QIAmp DNA Blood Kit (Qiagen). Conditions for PCR and targeted sequencing of pfcrt exon 2 (harboring codons 72-76) and polymorphic regions of pfmdr1 were previously described (16). A 121-bp fragment encompassing the complete exon 10 of pfcrt (harboring codon 350) was PCR-amplified and Sanger-sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that a significant proportion of P. falciparum parasites from French Guiana have a CQ IC 50 below the adopted resistance threshold of 100 nM, despite elevated prevalence of K76T, suggesting a reduced predictive value of this marker, at least in this region of South America (16). In this study, we pursued a genotypic and phenotypic survey, including wholegenome sequencing and gene-editing experiments, which led us to identify a molecular marker of drug susceptibility.…”
mentioning
confidence: 99%
“…trouve que nos données indiquent que certains marqueurs pertinents pour prédire la résistance aux antipaludiques dans certaines régions (comme l'Afrique par exemple) doivent être réévalués pour des contextes particuliers comme Madagascar [22] ou la Guyane française [23]. Ces données indiquent que l'évolution des populations parasitaires diffère dans différents contextes épidémiologiques et géographiques.…”
Section: Le Développement De Nouveaux Outilsunclassified
“…This possibility is suggested by the observation that recurrent isolates were significantly more likely to have multiple pfmdr1 copies (53/65 [81.5%]) than admission isolates (377/726 [51.9%]; P < .001, Fisher exact test). Another explanation is that parasites having a single pfmdr1 copy may be overexpressing pfmdr1 mRNA, as described in South America [8]. These 2 hypotheses require investigation.…”
mentioning
confidence: 99%